Fine-Needle Aspiration Is Suitable for Breast Cancer BRCA Molecular Assessment: A Case Report - Francesco Pepe; Pasquale Pisapia; Gianluca Russo; Mariantonia Nacchio; Elena Vigliar; Mario Giuliano; Umberto Malapelle; Giancarlo Troncone; Claudio Bellevicine (MDPI AG, 2021)
Breast cancer is the most common cause of cancer-related deaths in the female population worldwide. To the best of our knowledge, breast cancer (BRCA)1/2 gene mutations have not been described yet on breast cancer cytological specimens. Here we describe the case of a 38-year old woman with a family and personal history for breast cancer, who underwent a fine needle aspiration (FNA) procedure for a novel 30 mm lesion located in the external quadrants of the contralateral (left) breast. Cytological findings and ancillary immunostaining confirmed the diagnosis of a triple negative NST carcinoma. BRCA1/2 molecular assessment was carried out on DNA extracted from cytological (November 2020), biopsy (December 2014) and surgical resection (July 2015) specimens, as well as on the resection of a benign fibroadenoma, by using a next generation sequencing approach. Molecular analysis showed a pathogenic BRCA1 insertion (c.5266dupC; p.Q1756PfsTer74) in the cytological specimen (allelic fraction 92.0%), biopsy (allelic fraction 84.2%), surgical resection (allelic fraction 87.8%) and fibroadenoma (58.9%), demonstrating a germinal BRCA mutated status.